Protestant biblical interpretation a textbook of hermeneutics - Ramm, Bernard L. 1916-1992 (Grand Rapids, MI Baker, 1970)
Includes bibliographical references and indexes.
1999 reprint
Keywords: Bible -- hermeneutics